Sports Medicine in Transition - Ticinesi A; 2; Tana C; Nouvenne A; Meschi T; 2 (Deutsche Zeitschrift für Sportmedizin)
In the last decade, scientists have accumulated increasing evidence showing that the human gut microbiota, i.e. the ensemble of bacteria symbiotically living in the intestinal lumen of every individual, is involved in many aspects of human physiology and, possibly, disease. In fact, specific alterations of the gut microbiota, generally referred with the term of dysbiosis, have been detected in a large number of acute and chronic diseases, not involving only gastroenteric system. The microbiota may exert its influence on distant organs with multiple mechanisms, involving modulation of inflammation, anabolism, insulin sensitivity, bioavailability of nutrients, release of toxins, and metabolically active mediators. In this short review, we summarize the basis of the gut-muscle axis hypothesis, that is, the possible influence exerted by gut microbiota composition on skeletal muscle metabolism and function. This hypothesis is particularly focused on the pathophysiology of sarcopenia, the age-related loss of muscle mass and function associated with a large number of adverse outcomes in older people. Although no human studies support the possible involvement of gut microbiota in the onset of sarcopenia, some studies performed on mouse models seem to support the assumption that the age-related decline in muscle mass and function is associated with a distinct gut microbiota composition towards dysbiosis. More studies should thus investigate the possible connections between gut microbiota and muscle health. KEY WORDS: Microbiota, Sarcopenia, Mobility Limitations, Aging, Inflammation, Muscle Mass, Muscle Function